Children With ADHD Symptoms: Who Can Do Without Specialized Mental Health Care?. Issue 1 (January 2020) - Levelink, Birgit; Feron, Frans J. M.; Dompeling, Edward; van Zeben-van de Aa, Dorothea M. C. B.
Objective: A new Dutch Child and Youth Act should reduce specialized mental health care for children with symptoms of ADHD. Characteristics of children referred to a specialized ADHD clinic are explored to give direction to this intention.Method: Data of 261 children who underwent a multidisciplinary best practice evaluation (including rating scales, and demographic, psychological, and somatic findings) were analyzed. Univariable and multivariable logistic regression models were used to find predictive variables for the need of specialized mental health care.Results: Collected data were heterogeneous. (Sub)clinical total scores on the Teacher Report Form (TRF) and Child Behavior Checklist (CBCL) were predictive variables for specialized mental health care. Also children with divorced parents were more often referred to specialized care.Conclusion: (Sub)clinical scores on the CBCL and TRF increased the need for specialized care, but comprehensive assessment of every child with ADHD symptoms was necessary to differentiate between levels of care.